Academic Librarian Search Committee Members Identify Inclusivity Concerns with On-Campus Interview Practices / Houk, K. & Neilson, J. (2023). Inclusive hiring in academic libraries: A qualitative analysis of attitudes and reflections of search committee members. College and Research Libraries, 84(4), 568-588. https://doi.org/10.5860/crl.84.4.568 - Shen, Lisa (Evidence Based Library and Information Practice, 2024)
Objective – To understand how academic librarian search committee members’ perceptions and attitudes affect the equitability and inclusiveness of the on-campus interview process.Design – Thematic text analysis of open-ended responses to short-answer questions from an online survey.Setting – Online survey conducted between February and March of 2021.Subjects – 166 academic librarians who had served on hiring committees for academic librarians in North America between 2016 and 2020.Methods – Participants for the 33-question survey were recruited through several academic library listservs and social media postings on Facebook, LinkedIn, and Twitter. The researchers first individually reviewed and coded all responses for short answer survey questions, then reviewed the codes together. Finally, a thematic map was developed after the researchers reached a consensus on their shared approach to coding and generating clusters of meanings.Main Results – Six major clusters were identified through thematic coding of participants’ text responses concerning their experiences of on-campus interview practices as hiring committee members. These themes represented challenges to the inclusiveness of academic librarian searches, and included search committees’ treatment of the interview process as either intentional or situational tests (1), reliance on the ambiguously defined selection criteria of fit (2), experience with varying levels of commitment to diversity, equity, inclusion, antiracism, and accessibility (DEIAA) values (3), frustration with prevalence of institutional bureaucracy throughout the hiring process (4), and uneven adoptions of inclusive hiring (5) or reflective practices (6). The researchers also noted a common respondent mistake of misinterpreting equal (i.e., identical) treatment of candidates as evidence of equitable interview practices.Conclusion – Findings from this study highlighted the importance of academic institutions and hiring committees adopting reflective practices to critically and intentionally incorporate DEIAA-informed practices in planning and conducting academic librarian searches. The authors also stressed the need to reduce possible biases in hiring practices favoring candidates who conforms to White, ableist, and heteronormative culture and values. Examples of these efforts included considering the necessity of each interview element for assessing candidate performances, proactively ensuring full accessibility of the interview itinerary, and operationalizing the definition of “fit” in assessing candidates’ abilities.